Mechanisms Underlying Neuroprotection by the NSAID Mefenamic Acid in an Experimental Model of Stroke - Khansari, Parto S.; Halliwell, Robert F. (Frontiers in Neuroscience, 2019)
Stroke is a devastating neurological event with limited treatment opportunities. Recent advances in understanding the underlying pathogenesis of cerebral ischemia support the involvement of multiple biochemical pathways in the development of the ischemic damage. Fenamates are classical non-steroidal anti-inflammatory drugs but they are also highly subunit-selective modulators of GABAA receptors, activators of IKS potassium channels and antagonists of non-selective cation channels and the NLRP3 inflammosome. In the present study we investigated the effect of mefenamic acid (MFA) in a rodent model of ischemic stroke and then addressed the underlying pharmacological mechanisms in vitro for its actions in vivo. The efficacy of MFA in reducing ischemic damage was evaluated in adult male Wistar rats subjected to a 2-hr middle cerebral artery occlusion (MCAO). Intracerebroventricular (ICV) infusion of MFA (0.5 or 1mg/kg) for 24 hours, significantly reduced the infarct volume and the total ischemic brain damage. In vitro, the fenamates, MFA, meclofenamic acid, niflumic acid and flufenamic acid each reduced glutamate-evoked excitotoxicity in cultured embryonic rat hippocampal neurons supporting the idea that this is a drug class action. In contrast the non-fenamate NSAIDs, ibuprofen and indomethacin did not reduce excitotoxicity in vitro indicating that neuroprotection by MFA was not dependent upon anti-inflammatory actions. Co-application of MFA (100µM) with either of the GABAA antagonists picrotoxin (100µM) or bicuculline (10µM) or the potassium channel blocker TEA (30mM) did not prevent neuroprotection with MFA, suggesting that the actions of MFA also do not depend on GABAA receptor modulation or potassium channel activation. These new findings indicate that fenamates may be valuable in the adjunctive treatment of ischemic stroke.